From Reflection to Practice: A Qualitative Study of Teaching Practicum Experiences - Anis, Muhammad Ibne; Hasan, Md. Mahadhi (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This research explores the impact of the Teaching Practicum and Classroom Management course on the development of my pedagogical philosophy, lesson design, resource selection, and instructional methods in the context of TESOL. A qualitative reflective approach and in-depth interview with five student-teachers were used to explicate the learning gained during the teaching practicum that was part of the MA in Applied Linguistics and TESOL program. The research points out that reflection, feedback from instructors and peers, and self-evaluation are crucial in developing effective teaching strategies and mindsets. The practicum provided an interactive context that focused on active pedagogical approaches and peer cooperation. The findings highlight the fundamental importance of reflective practice, supportive feedback, and micro-teaching opportunities in the enhancement of my teaching skills and confidence. In addition, the study highlights the importance of cultural competence, flexibility, and ongoing professional development for future TESOL teachers. The results of this study suggest that professional development programs for teachers should focus on hands-on teaching experience, collaborative learning opportunities, and continual training to better prepare teachers for the dynamic challenges ahead as effective instructors. This study was conducted within a smaller-scale classroom setting, and future research directions include further development of these pedagogical methods and reflective tools in larger-scale classrooms to gauge their impact and effectiveness.